Pengaruh Earning Per Share, Return On Equity, Debt To Equity Rasio, Dan Deviden Payout Rasio Terhadap Harga Saham Pada Perusahaan Manufaktur (Studi Empiris Pada Perusahaan Manufaktur) Yang Go Publik Di Bursa Efek Indonesia Periode (2017-2021) - Hefni Oktafia Tarigan Tondang; Kharen Heberina Br Tarigan; Wirda Lilia; Julienda Br Harahap (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Manufacturing Companies in the Consumer Goods Sector Listed on the Indonesia Stock Exchange for the 2017-2021 period. The share price of each company listed on the Indonesia Stock Exchange has a major influence on the company's performance. Therefore, researchers conducted research using the dependent variable, namely stock prices, which were then followed by independent variables, namely Earning Per Share, Return On Equity, Debt To Equity Ratio, and Dividend Payout Ratio. As for companies that experience an increase every year, this does not affect their share price. The data analysis method used is a logistic regression analysis method that uses partial tests, simultaneous tests, and tests of the coefficient of determination. The results showed that stocks have a return on equity and the debt to equity ratio has a negative impact on stock prices. Keywords: Earning Per Share, Return On Equity, Debt To Equity Ratio, Dividend Payout Ratio to Stock Price